PENERAPAN METODE MARK UP PRICING BERBASIS FULL COSTING DALAM MENENTUKAN HARGA JUAL PRODUK - Basyir, Ashar; Erny Pratiwi; Dyah Palupi; Dini Dwi Ermawati (Jurnal Aplikasi Perpajakan, 2025)
This scientific paper aims to evaluate the selling price determined by the company and compare it with the selling price calculated using the mark-up pricing method, based on the full costing method of calculating the cost of production. This study uses primary data, with data collection methods including interviews and observation. The results of this research show a difference between the selling price set by the company and the one calculated using the mark-up pricing method. The company’s calculation resulted in a value of Rp 20,384, which was rounded down to Rp 20,000, while the mark-up pricing method yielded a value of Rp 23,776.98. This difference is due to the fact that the company has not accounted for all costs involved in the production cost calculation process.